Estimating post-pandemic effects of working from home and teleconferencing on travel behaviour - Faber, Roel; Hamersma, Marije; de Haas, Mathijs; Krabbenborg, Lizet; 't Hoen, Arjen (European Journal of Transport and Infrastructure Research, 2023)
Like in many other countries, the Dutch government instructed people to work from home where possible during the COVID-19 pandemic to halt the transmission of the virus. This policy seems to have resulted in a structural increase in working from home and teleconferencing that will outlast the pandemic. However, the longer-term effects on travel behaviour are still unclear. Making use of panel data collected using the Netherlands Mobility Panel, this paper has two main aims. First, it analyses developments in working from home and teleconferencing since COVID-19. Second, it estimates the expected post-pandemic effects on travel behaviour. The results show that compared to before the pandemic, the average number of hours that people work from home has doubled and roughly two-thirds of respondents indicate that they teleconference more often. We estimate that structural, post-pandemic increases in working from home and teleconferencing will result in a negative effect on distances travelled by train (-3% to -9%), by bus, tram, and metro (-1% to -5%) and car (-1 to -5%). The estimated effect on the distance travelled by bicycle (-2% to 0%), and walking (0% to +1%) is smaller or even positive, due to people making more complementary trips for other purposes when working from home. When interpreting these results, we should keep in mind that due to various other factors, such as population growth, total travel demand will still grow in the near future.